HARTA KARUN ITU CANDI BATA YANG UNIK - Baskoro Daru Tjahjono (BRIN, 2003)
A site located in Candi, Menoreh Village, Salaman District, Magelang Regency was looted. The residents call the site as Wurung Temple, because it is considered as an unfinished temple. Several years ago the site, which was located on land belonging to Hadi Prayitno, was excavated by a group of people. The local community did not know their origin and the purpose of the excavation. Only word of mouth got out that their goal was to find treasure. Whether they found it or not, they just left the excavated hole. The site was abandoned after the illegal excavation took place. The land owner did not even know what he was going to do, so that the rice field, which was actually productive, was left without planting anything.